Alkuopetusikäisen valmius reflektoida matemaattisessa ongelmanratkaisutilanteessa - Eronen, Lasse; Toikka, Susanna (FMSERA Journal, 2021)
A meaningful self-assessment basis on reflection. On the other hand, there is a positive connection between problem-solving skills and skills of reflection. Therefore, the mathematical problem-solving situation is a natural situation to develop reflection skills. This article examines the interview material of grades 1-2 students (n = 23) collected in a problem-solving situation. We first look at students ’feelings about problem-solving and studying mathematics, as well as their perceptions of what mathematics is. Second, we look at students ’willingness to produce reasoned answers (reflections) to previous questions. The research reveal that the problem-solving, mathematics as a subject as well as the study of mathematics, provide the students with emotional experiences of comfortable and uncomfortable states, both easy and difficult, through the perceived moments. Students ’reflections could be classified into four groups according to how many of the interview questions the pupil was able to give a reasoned answer. The mathematical problem-solving situation provided an opportunity to practice reflection, as it was strongly associated with experientiality and emotional fluctuations. The defined reflection groups follow the reflection skill descriptions presented in theory, which in turn shows the importance of the practice of reflection also in primary education.